Web application for pharmacy information system - Chew, Chee Hau (2015)
Pharmacy Information System is a web application that manages pharmacy data, it aims to link all pharmacies in Singapore together and manage them in a single centre control using the same database, help pharmacies to improve their work flow and keep tracking of inventory, patients information are also share among each other. There are a total of 6 sections, Pharmacy Management, Account Management, Category Management, Medicine Management, Sale Management and Inventory Management. The project is developed in Visual Studio 2012, ASP.net to develop web application, C# as the programming, SQL Server 2012 for the database using ADO.net for data access. Version one of the project is able to perform all basic function for operating a pharmacy, however the system is not stable due to the lack of opportunity for mass system testing from pharmacies all over Singapore, therefore there are a lot of many unforeseen incident, such as connection time out during data transmission, declining in system performance when the database get larger overtime, bugs that may discovered over time, vulnerability against cyber-attack since the only security now is password encryption. Therefore an upgrade of the system and more testing is required before actual deployment.